Using MQTT and Node-RED to monitor the ATLAS Meta-data Interface (AMI) stack and define metadata aggregation tasks in a pipelined way - Odier, Jérôme; Lambert, Fabian; Fulachier, Jérôme; Jaume, Maxime; Delsart, Pierre-Antoine (EPJ Web of conferences, 2024)
ATLAS Metadata Interface (AMI) is a generic ecosystem for metadata aggregation, transformation and cataloging. Each sub-system of the stack has recently been improved in order to acquire messaging/telemetry capabilities. This paper describes the whole stack monitoring with the Message Queuing Telemetry Transport (MQTT) protocol and Node-RED, a tool for wiring together hardware/software devices. Finally, this paper shows how Node-RED is used to graphically define metadata aggregation tasks, in a pipelined way, without introducing any single point of failure.